2020
DOI: 10.3390/su12114467
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Green Innovation, Social Entrepreneurship, and Sustainable Development

Abstract: Economic growth is one of the important objectives of economic policy due to the beneficial effects it has on employment and economic well-being. The work carried out in the last few decades has highlighted the roles that entrepreneurship and innovation play in promoting this objective. However, the environmental deterioration resulting from policies implemented to stimulate growth has led to considerations of other objectives that are more compatible with the defense of the environment, such as sustainable de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 93 publications
2
37
0
Order By: Relevance
“…The environmental situation of the economies has led to the need to include this problem in the analysis of economic growth. In this sense, there are two opposite approaches: approaches that consider that environmental restrictions do not affect growth and those that, on the contrary, affirm that the lack of natural resources will end up impeding economic growth ( Acs et al, 2018 , Demirel and Kesidou, 2019 , Galindo-Martín et al, 2020a ). Those in accordance with the second position should rethink the objective of economic growth to try to carry out an economic activity that does not compromise the situation of future generations.…”
Section: Theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental situation of the economies has led to the need to include this problem in the analysis of economic growth. In this sense, there are two opposite approaches: approaches that consider that environmental restrictions do not affect growth and those that, on the contrary, affirm that the lack of natural resources will end up impeding economic growth ( Acs et al, 2018 , Demirel and Kesidou, 2019 , Galindo-Martín et al, 2020a ). Those in accordance with the second position should rethink the objective of economic growth to try to carry out an economic activity that does not compromise the situation of future generations.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Therefore, instead of the traditional objective of growth, this paper considers the objective of sustainable development. In achieving this objective, entrepreneurship is also a factor to consider since actions aimed at improving the environment represent a business opportunity ( Galindo-Martín et al, 2020a , Hall et al, 2010 , Öykü İyigün, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of entrepreneurship goes beyond the economic and the social; entrepreneurship effectively engages in addressing environmental issues as well [3]. The notion of "green innovation" is, therefore, an extension of the definition of entrepreneurship which is considered as a social agent that reacts to market imperfection [4]. Entrepreneurship is also considered a byproduct of institutional inefficiency and such a conceptualization is particularly relevant when it comes to issues of sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…The gap between environmental goals and the reality is still left largely unfilled and presents as an opportunity for entrepreneurs. Opportunity-driven entrepreneurship is a series of reactive or proactive behaviors to such demands [4].…”
Section: Introductionmentioning
confidence: 99%
“…Porter and Van der Linde [19] suggested that an important issue in measuring net compliance costs of environmental regulations are also the benefits from the innovation induced by it [58], which, however, varies across sectors. Competitive enterprises can address environmental problems in an innovative way, which can stimulate sustainable development [59] and simultaneously reflect in lower compliance costs of environmental regulations. The formula for success must include innovative solutions that promote both environmental and industrial competitiveness in different economic sectors.…”
Section: Economic Sectormentioning
confidence: 99%